(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
Juniperus virginiana has a pyramidal branch, which in its natural state forms a branched and sparse branch. For landscaping purposes, it is necessary to artificially shape tree branches. In terms of the density of its branches, juniper virginiana belongs to the group of compact trees.